Characterization of α-Glucosidase Inhibitor Streptomyces sp. IPBCC.a.29.1556 Aqueous Extract: An Endophyte of Indonesian Ficus deltoidea - Isra Janatiningrum; Yulin Lestari; Dedy Duryadi Solihin; Anja Meryandini (Universitas Gadjah Mada, 2022)
Filamentous bacteria have been known as actinobacteria which could produce various secondary metabolites, including an α-glucosidase inhibitor. The α-glucosidase inhibitor has been identified to be potentially valuable for the treatment of diabetes mellitus. Endophytic actinobacteria are able to produce bioactive compounds that are similar to their hosts. Indonesian Ficus deltoidea is one of the medicinal plants which has the activity of the α-glucosidase inhibitor. The α-glucosidase inhibitor has been characterized by optimizing compound production, fractionation, analysis using TLC and LC-MS, and identifying inhibitor mechanisms. The α-glucosidase inhibitor substance is present in Streptomyces sp. IPBCC.a.29.1556 aqueous extract. The aqueous extract was separated and fraction 1 had an IC50 value of 58.8 μg/mL, which is better than acarbose (IC50 = 90.4 μg/mL). Kinetic studies revealed that this fraction inhibited the enzyme through a non-competitive mechanism. Chemical profile based on LC-MS, fraction 1 showed the presence of Phenylpropynal, Butyric acid, 2-(2-Ethoxyethoxy)ethanolate, 1,1-Diethoxyethane acetate, N,N-dimethyl-3-oxide-1H-Benzotriazole-1-propanamine, p-coumaric acid, and isoquinolinium which might contribute individually or synergistically to the observed α-glucosidase inhibitor activity. These results suggest that fraction 1 from the aqueous extract of Streptomyces sp. IPBCC.a.29.1556 is the potential source to produce an α-glucosidase inhibitor for the management of postprandial hyperglycemia.